Implementation of Problem Based Learning Model to Improve the Ability to Solve SPLDV in Grade 9 Students - Mazro’atul Akhiroh; Rudianto Artiono; Kamadiyati Rachman (Jurnal Impresi Indonesia, 2024)
This research focuses on the challenges in learning mathematics, especially in understanding and solving the system of linear equations of two variables, which is often an obstacle for students. This study aims to improve students' ability to solve SPLDV as well as increase students' motivation and engagement in learning. This study analyzed the effectiveness of Problem Based Learning (PBL) model in improving the ability to solve the System of Linear Equations of Two Variables (SPLDV) in class VIII students of SMPN 54 Surabaya. This study involved 34 students consisting of 18 male students and 16 female students using a Classroom Action Research (PTK) approach carried out in two cycles, each of which consisted of planning, action implementation, observation, and reflection stages. The instruments used were learning outcome tests, observation sheets, and student questionnaires. The results showed a significant increase in students' SPLDV problem solving ability, with the average score of students increasing from 65 in the pretest to 75 in the first cycle post-test, and reached 85 in the second cycle post-test. The proportion of students who met the Minimum Completion Criteria (KKM) increased from 50% in the first cycle to 85% in the second cycle. Further analysis showed that female students outperformed male students, with an average score of 87 and 82. Student engagement also increased, reaching 90% in the second cycle. This study concludes that the PBL model effectively improved SPLDV problem solving skills in grade 9 students and recommends its wider application in mathematics education.